A Simple Wavelet-Based Test for Serial Correlation in Panel Data Models - Yushu Li; Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2013)
Hong and Kao (2004) proposed a panel data test for serial correlation of unknown form. However, their test is computationally difficult to implement, and simulation studies show the test to have bad small-sample properties. We extend Gencay's (2011) time series test for serial correlation to the panel data case in the framework proposed by Hong and Kao (2004). Our new test maintains the advantages of the Hong and Kao (2004) test, and it is simpler and easier to implement. Furthermore, simulation results show that our test has quicker convergence and hence better small-sample properties.
Keywords: C11; C12; C15; 330; energy distribution; MODWT; serial correlation; static and dynamic panel models